Pengaruh Konsentrasi Tepung Sorgum dan Tepung Daun Katuk Terhadap Sifat Sifat Fisik, Kimia dan Hedonik Cookies - Siti Lestari; Yossi Wibisono (Politeknik Negeri Jember, 2023)
Cookies are a type of dry cake that is similar to biscuits and is popular in Indonesia. This research aims to determine the effect of the concentration of sorghum flour and katuk leaf flour on the physical, chemical and hedonic properties of cookies and determine the product with the best treatment. This research used a Randomized Block Design with 5 treatments adding katuk leaf flour (0%, 5%, 10%, !5% and 20%) and 3 replications. The research results showed that the concentration of sorghum flour and katuk leaf flour had a significant effect on the hedonic test and the hedonic quality of color, taste and aroma, as well as on the color test results (L, a, b). However, it had no real effect on water content, carbohydrates, protein, texture as well as hedonic tests and hedonic quality of texture. Treatment P1, namely adding 5% katuk leaf flour to the cookies, gave the best results from the hedonic test and hedonic quality and color (L, a, b).